Investigating the Sleep Quality and its Relationship with the Job Stress and Mental Load in Firefighters: A Case Study in Isfahan City - Heidari, Hamidreza; Dehghani, Omid (Shahroud Journal of Medical Sciences, 2025)
Background: This study aimed to investigate the quality of sleep and its relationship with the amount of occupational stress and mental workload in firefighters in Isfahan City. Methods: The research was a cross-sectional study with a descriptive-analytical approach. The statistical population includes all the firefighters of Isfahan city equal to 715 people, of which 124 personnel were selected as a sample by simple random sampling. Standard questionnaires including the NASA Workload Index (NASA-TLX), the Job Stress Questionnaire of the Health and Safety Institute of England (HSE), and the Pittsburgh Sleep Quality Questionnaire) were the tools used in this research. Results: The results showed that there is a moderate negative correlation between sleep quality and job stress (r=-0.59, P-value=0.001). The results of the mental load survey also showed that the average time pressure was 52.09±19.26, which is higher than the other dimensions of mental load, and the lowest dimension of mental load was related to failure and frustration (35.16±18.89). Conclusions: Based on the results of this study moderate and reverse relations were obtained between sleep quality and job stress as well as sleep quality and mental workload. In addition, the number of the missions of the firefighters determined as an influencing factor on increasing the mental workload. While doing regular exercise led to better sleep quality for firefighters. These findings can be used by policymakers in this field to improve the sleep quality of firefighters and reduce associated health problems.